2006
DOI: 10.1002/ar.a.20286
|View full text |Cite
|
Sign up to set email alerts
|

Connecting thalamus and cortex: The role of ephrins

Abstract: The complex task of wiring up the brain during embryonic development is achieved by a multitude of guidance signals acting in complex combinations to drive growing axons to their proper targets. The somatosensory system provides an extensively studied model system featuring many universal mechanisms of neural development. In rodents, it constitutes an important model to study how precise topographic connections are achieved. Recent evidence suggests that the Eph/ephrin family of guidance molecules is of pivota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 79 publications
0
38
0
Order By: Relevance
“…On the other hand, this generation coincides with the establishment of the descending corticothalamic projection (Jones, 1997;Uziel et al, 2006). This notion is supported by evidence that (1) layer VI, the source of most corticothalamic projections, has a considerable number of neurotrophin-expressing neurons Miller, 1995, 2000) and (2) the thalamus does not have neurons capable of manufacturing a neurotrophin(s) (Baquet et al, 2004), but it does have cells that express neurotrophin receptors (Vitalis et al, 2002;present study).…”
Section: Factors Influencing Postnatal Neuronogenesismentioning
confidence: 66%
“…On the other hand, this generation coincides with the establishment of the descending corticothalamic projection (Jones, 1997;Uziel et al, 2006). This notion is supported by evidence that (1) layer VI, the source of most corticothalamic projections, has a considerable number of neurotrophin-expressing neurons Miller, 1995, 2000) and (2) the thalamus does not have neurons capable of manufacturing a neurotrophin(s) (Baquet et al, 2004), but it does have cells that express neurotrophin receptors (Vitalis et al, 2002;present study).…”
Section: Factors Influencing Postnatal Neuronogenesismentioning
confidence: 66%
“…Feldheim et al [10] described ephrinA5 mRNA expression from E14.5, in the dorsal and ventral lateral geniculate nuclei in a ventral, lateral and anterior (high) to dorsal, medial and posterior (low) gradient. Between E16.5 and E18.5, nuclei of the lateral part of the dorsal thalamus [27] and ventral nuclei [29] both exhibit ephrinA5 mRNA. Our results partially match with these previous studies, as we showed here that ephrinA5 protein was strongly expressed in the thalamus in a ventral and rostral (high) to dorsal and caudal (low) gradient especially from E12.5 to E16.5.…”
Section: Discussionmentioning
confidence: 99%
“…In the telencephalon, ephrinA5 mRNA is expressed in the olfactory system [17,18], in the lateral and medial ganglionic eminences and their ventricular zones [19-21] and in the cortex [22-27]. EphrinA5 transcript expression has been also detected in the diencephalon (hypothalamus and thalamus) [10,21,27-29] and in the inferior and superior colliculi as well as in the pretectal nuclei and the red nucleus of the mesencephalon [28,30,10,21]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential component of the subplate zone is the extracellular matrix, which builds up to 70% of the neuropil . The extracellular matrix of the subplate contains different attractant and repellent molecules, such as fibronectin (Chun & Shatz, 1988;Tuttle et al 1995;Pearlman & Sheppard, 1996), semaphorins, ephrins and other molecules (Hoerder-Suabedissen et al 2009; for reviews see Judaš et al 2003;Uziel et al 2006). The possible cellular sources of the extracellular matrix and axonal guidance molecules are subplate cells (neurons or glia).…”
Section: Efferent Pathwaysmentioning
confidence: 99%